Study of Surficial Sediment Characteristics and Distribution in the Continental Shelf of the North Tartous City Depending on Grain Size Analysis - غدير سامر; بعلة محمد; شيحة هبة (Latakia University Journal -Basic Sciences Series, 2021)
Detailed sedimentary study of the surficial sediments of section of the Syrian continental shelf in the north of Tartous city depending on grain size analysis has been carried out in order to determine the distribution pattern of surficial sediments, understand depositional process and environments in the study area. The grain size parameters for 68 surficial sediments samples revealed three types of sediments: sand, silt and clay in various ratios, medium grain size, well sorted to poorly sorted, negatively to very negatively skewed and mesokurtic, This results are loaded to plot digital maps to the study area. Wherever the high energy wave helped to disperse the sediments along the Syrian continental shelf and dispersing them it by littoral current to the open ocean. That indicate the sediments have been deposited in moderate to high conditions and the energy conditions are changed with the depth.